2015
DOI: 10.1111/jgs.13820
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal Cognitive Assessment—Basic: A Screening Tool for Mild Cognitive Impairment in Illiterate and Low‐Educated Elderly Adults

Abstract: The MoCA-B appears to have excellent validity and addresses an unmet need by accurately screening for MCI in poorly educated older adults regardless of literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(183 citation statements)
references
References 19 publications
8
169
4
2
Order By: Relevance
“…One study (N=85) in Thailand [53], suggested a cut off of 24/25 in a poorly educated sample. One study (N=152) in Korea [21] suggested a cutoff of 22/23 with a 1 point adjustment for <6 years of education.…”
Section: South East and Southern Asia (Japan Korea Philippines Srimentioning
confidence: 99%
See 1 more Smart Citation
“…One study (N=85) in Thailand [53], suggested a cut off of 24/25 in a poorly educated sample. One study (N=152) in Korea [21] suggested a cutoff of 22/23 with a 1 point adjustment for <6 years of education.…”
Section: South East and Southern Asia (Japan Korea Philippines Srimentioning
confidence: 99%
“…One study (N=152) in Korea [21] suggested a cutoff of 22/23 with a 1 point adjustment for <6 years of education. Julayanont et al [53] made an adjustment of 1 point for < 4 years education and an additional 1 point for meeting the illiteracy criteria. All studies displayed high sensitivity and specificity, but these results were based on small samples.…”
Section: South East and Southern Asia (Japan Korea Philippines Srimentioning
confidence: 99%
“…Its role is controversial, as some authors had suggested potential risks of overdiagnosis due to too severe norms of the AAN revised criteria [43,44]. Moreover, we recently showed that aviremic patients with ANI do not display the same pattern of immune activation than MND, suggesting that this definition is not stringent and not represent overt disease, or that it is a pre-clinical condition of more severe forms of impairment [34]. However, others have showed that patients with ANI have higher risks to deteriorate over time than unimpaired subjects [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…It scores a maximum of 30 points and results below 26 are considered as pathological. In case of education level below high school, 1 point is added to the final score [34] A local battery, suggested by French national guidelines for the management of HAND [35] and named FIMF as abbreviation of 4 sub-tests initials included:…”
Section: Screening Toolsmentioning
confidence: 99%
“…Participants who spoke Mandarin, Spanish, or Tagalog as their native language completed the MoCA in their respective native languages. Participants in the Somali cohort completed a new Somali translation of the MoCA Basic (MoCA-B) that was deemed to be culturally acceptable, and appropriate given participants' lower education levels (Julayanont et al, 2015). Participants who were administered the MoCA-B were also given the forward and backward digit span subtest from the MoCA.…”
Section: Cognitive Tasksmentioning
confidence: 99%